2011
DOI: 10.4162/nrp.2011.5.5.421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-lipoic acid and L-carnosine supplementation on antioxidant activities and lipid profiles in rats

Abstract: α-Lipoic acid and L-carnosine are powerful antioxidants and are often used as a health supplement and as an ergogenic aid. The objective of this study was to investigate the effects of α-lipoic acid and/or L-carnosine supplementation on antioxidant activity in serum, skin, and liver of rats and blood lipid profiles for 6 weeks. Four treatment groups received diets containing regular rat chow diet (control, CON), 0.5% α-lipoic acid (ALA), 0.25% α-lipoic acid + 0.25% L-carnosine (ALA + LC), or 0.5% L-carnosine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 50 publications
3
42
2
1
Order By: Relevance
“…Alpha-lipoic acid (ALA), chemically named 5-(1,2-dithiolan-3-yl) pentanoic acid (C 8 H 14 O 2 S 2 ), is a naturally occurring compound which is found in plants and animals and functions as anti-oxygen in virtually all body tissues [35,36]. In humans, ALA is mainly synthesized in tissues with highly metabolic activities like the liver, kidney, and heart [37]. ALA, which is traditionally known as one of the requisite cofactors in mitochondrial respiratory enzymes, is capable of scavenging reactive oxygen species and free radicals to keep the redox homeostasis in the cells and recycling endogenous antioxidants like Vitamin C, Vitamin E, and GSH [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-lipoic acid (ALA), chemically named 5-(1,2-dithiolan-3-yl) pentanoic acid (C 8 H 14 O 2 S 2 ), is a naturally occurring compound which is found in plants and animals and functions as anti-oxygen in virtually all body tissues [35,36]. In humans, ALA is mainly synthesized in tissues with highly metabolic activities like the liver, kidney, and heart [37]. ALA, which is traditionally known as one of the requisite cofactors in mitochondrial respiratory enzymes, is capable of scavenging reactive oxygen species and free radicals to keep the redox homeostasis in the cells and recycling endogenous antioxidants like Vitamin C, Vitamin E, and GSH [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-Lipoic acid is a substance with antioxidant properties that easily penetrates the skin as a result of its lipid soluble characteristics as well as its low molecular weight (Beitner 2003). According to Kim et al (2011), Freisleben et al (1994) observed that topical α-lipoic acid cream applied to hairless mice penetrates the epidermis and is distributed in the dermis and the subcutaneous tissue after 4 h. This revelation and the fact that enhanced protection of human cells against ultraviolet light by antioxidant combinations involving dietary carotenoids has been earlier observed are suggestive of the role of UVB on tissue damage exhibited by sun-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…3 The N-terminal part is a fragment of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and the C-terminal part is the other bioactive dipeptide L-carnosine capable of scavenging hydroxyl radicals (Table 1). 6 A fragment of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) contains residues Trp, 2 Asn, 5 Gly 8 and Tyr, 9 which are necessary for interaction of the peptide with the GalR2 receptor 7,8 and thereby to trigger cardioprotective effects. L-carnosine tailing to C-terminal part of peptide G1 enhances its resistance to the action of exopeptidases due to the insertion of βAla14.…”
Section: Structure and Properties F Of Peptide G1mentioning
confidence: 99%
“…Post-ischaemic administration of the peptides improved functional recovery of isolated perfused rat hearts and reduced infarct size in rats in vivo. 4,5 The chimeric ligand [βAla14, His15]-galanin (2-15) (G1), which is composed of galanin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and the dipeptide carnosine, exhibited the most beneficial effect. 3 The mechanisms of action of peptide G1 remain unclear.…”
mentioning
confidence: 99%